Imaging resin infiltration into non-cavitated carious lesions by optical coherence tomography. (May 2017) - Schneider, Hartmut; Park, Kyung-Jin; Rueger, Claudia; Ziebolz, Dirk; Krause, Felix; Haak, Rainer
Abstract: Objectives: Visualisation of the etching process and resin penetration at white spot carious lesions by spectral domain optical coherence tomography (SD-OCT). Materials and methods: The non-cavitated carious lesions (ICDAS code 2) of four visually preselected extracted human molars and premolars were verified as enamel lesions by micro computed tomography (μCT). One region of interest (ROI) per tooth was marked by two drill-holes in occlusal-cervical direction. The lesions were imaged by SD-OCT. Lesions were infiltrated (Icon, DMG) according to the manufacturer's instructions. During each treatment step and after light curing of the infiltrant, the ROIs were imaged again by SD-OCT. Teeth were sectioned through the ROIs and section layers were imaged by scanning electron microscopy in order to compare with the OCT images. The image sequences for etching and infiltration were viewed in time lapse. Results: During the etching process, numerous bubbles formed on the lesion surface. Using OCT, the process of resin penetration into the carious lesion body became visible. The early enamel carious lesion was completely infiltrated by the resin whereas infiltration of the advanced enamel carious lesion was incomplete and inhomogeneous. Conclusion: Resin infiltration can be increased by optimizing the etching process. Optical coherence tomography provides information about the process and degree of resin infiltration. Clinical significance: Active acid application before resin infiltration is recommendable.